Comparison of air to air and air to water intercoolers in the cooling process of a turbocharger engine - Nasution, Henry (Penerbit UTM Press, 2015)
Compressed air from a turbocharger needs to be cooled down to prevent knocking inside the combustion chamber from occurring. In the present study, air to water intercooler is used as a heat exchanger to minimize the temperature rise of the charged air produced from the turbocharger i.e. water is used as the medium for cooling the temperature of the charged air before the intake manifold instead of using direct air, which is the common medium of any intercooling system. The experiments were conducted with engine speeds of 2000, 2500, 3000, 3500, 4000, 4500 and 5000 rpm, with pressure of 0.6, 0.8 and 1.0 bar. The present study found that the air to water intercooler is more efficient and the heat transfer is much better than that of the air to air intercooler. This is due to the air flow to the water inside the intercooler is better compared to the system that uses an air to air intercooler system.